Tingkat Pemahaman Peserta Didik Kelas VI Sd Terhadap Bahaya Merokok - Gilang Sasmita; Muhammad Abduh (Jurnal Elementaria Edukasia, 2023)
The smoking habit among students and teenagers is currently increasingly common. Students at the age of 10 years are already smoking, even though this age is the final stage of child development. This article discusses the level of students' understanding of the dangers of smoking with the aim of finding out the level of understanding of grade VI elementary school students about the dangers of smoking. This research was conducted at 10 schools consisting of 5 state elementary schools and 5 private elementary schools with A accreditation and having parallel classes. The research used a qualitative descriptive method in the form of a survey with data collection via questionnaires from 992 students at 10 schools. The data collection process was carried out during the research using the Miles and Hubermen model which includes four activities, namely data collection, data reduction, data presentation, conclusion drawing and verification. After data collection and data reduction, the data is then presented using a scoring technique which is divided into three levels, namely low, medium and high. The conclusion obtained is that students' understanding of the dangers of smoking is at a moderate level of understanding. Students' understanding can be proven by answers that are often answered correctly in multiple choice and essay questions. Students have the ability to describe their understanding of the dangers of smoking.